(untitled) (Palíndromo, 2023)
The research A/r/tographic in the territory of pedagogy aims to think the A/r/tography as a research methodology in the context of a Pedagogy course, understanding the role of the artist/researcher/teacher and academics, as (inter)speakers in artistic and cultural (re)invention and creation processes. The methodology has an A/r/tographic approach, with three Aesthetic Workshops developed over a semester. The choice was made by our desire to share experiences with Pedagogy academics, mobilized by music, modeling and craftsmanship, fields that connect with our training as artists/ researchers/ teachers. What drove us to thematic choice and methodology was the understanding that in a formative process, narratives educate us and move us to (re)invent the already invented. Art in its breadth and complexity enables the appropriation of reality and our imaginary power. The production of data was anchored in sound, visual and body narratives, having as conceptual/methodological basis, the interpretative analysis, translated into attitudes and ways of being and thinking. The processes/results indicated that the (inter)speakers, Pedagogy academics, understood the sense of training as an itinerary journey through the Arts and sensibilities. The Aesthetic Workshops potentiated the being together and the formative paths in an identity, ethical and aesthetic construction.